2016
DOI: 10.1093/gbe/evw043
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis Drives Rapid Gene Creation and Masculinization of the X Chromosome in Stalk-Eyed Flies (Diopsidae)

Abstract: Throughout their evolutionary history, genomes acquire new genetic material that facilitates phenotypic innovation and diversification. Developmental processes associated with reproduction are particularly likely to involve novel genes. Abundant gene creation impacts the evolution of chromosomal gene content and general regulatory mechanisms such as dosage compensation. Numerous studies in model organisms have found complex and, at times contradictory, relationships among these genomic attributes highlighting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 108 publications
5
19
1
Order By: Relevance
“…As an interesting contrast to our finding of Y-linked genes with male-limited expression, Baker et al [42] found genes only expressed in males to be enriched on the X chromosome of stalk-eyed flies. Their result seems more surprising than ours, and runs counter to the feminization (or demasculization) of expression patterns of X-linked genes reported in other studies [43][44][45].…”
Section: Identification Of Y-linked Markerscontrasting
confidence: 99%
See 1 more Smart Citation
“…As an interesting contrast to our finding of Y-linked genes with male-limited expression, Baker et al [42] found genes only expressed in males to be enriched on the X chromosome of stalk-eyed flies. Their result seems more surprising than ours, and runs counter to the feminization (or demasculization) of expression patterns of X-linked genes reported in other studies [43][44][45].…”
Section: Identification Of Y-linked Markerscontrasting
confidence: 99%
“…Nevertheless, it is unclear how often we ought to expect genes with male-limited expression to be on the Y chromosome. Note that the patterns of gene expression used in our study here were observed for genes expressed in nonreproductive tissues [31], whereas many of those reported by Baker et al [42] were gonadal.…”
Section: Identification Of Y-linked Markersmentioning
confidence: 61%
“…Maelstrom and aubergine have also duplicated within diopsids. We previously (Baker et al 2016) identified five duplicates of maelstrom, and here found an additional near-identical copy. Four of these six copies, including the adaptively evolving Xlinked copy appear to be novel within the genus Teleopsis (Figure S8).…”
Section: Discussionsupporting
confidence: 60%
“…However, intersecting these sperm proteome results with a nuanced dissection of gene expression indicates a possible dearth of X-linked sperm genes with testis-specific expression, depending on the gene-set analyzed (Meisel et al 2012). More recently, another species of fly, the stalk-eyed fly, was observed to have a masculinized X chromosome (Baker et al 2016). Thus, the pattern of sex-biased gene distribution is still far from clear; these sperm proteomic results from monarch and Carolina sphinx represent an important complement to similar analyses in XX/XY species by testing the same hypotheses in a set of independent sex chromosomes.…”
Section: Proportion Of Orthologs In Sperm Proteome By Locationmentioning
confidence: 99%